Since there is two negative signs in the original equation, you need two negative signs in the equivalent one as well.
Because one of the negatives if before the fraction, it doesn't matter if the second negative is on the 13 or on the 12.
The answer is A.
Answer:
no
Step-by-step explanation:
no. substitute -1 for x and -2 for y.
the first one is -1 - 10
this equals -11 not 3
Answer: ![y=10000(1.65)^x](https://tex.z-dn.net/?f=y%3D10000%281.65%29%5Ex)
Step-by-step explanation:
Given: The sales of 10000 increased by 65% each year .
Let x be the number of years.
The rate of growth=65%= 0.65
The exponential growth function is given by
![y=A(1+r)^x](https://tex.z-dn.net/?f=y%3DA%281%2Br%29%5Ex)
, where A is initial amount and r is the rate of growth in decimal.
Then the increase in the sales id given by :-
![y=10000(1+0.65)^x\\\Rightarrow\ y=10000(1.65)^x](https://tex.z-dn.net/?f=y%3D10000%281%2B0.65%29%5Ex%5C%5C%5CRightarrow%5C%20y%3D10000%281.65%29%5Ex)
All three sides are the same size
-------------------------------------------------------------------------------------
Formula
-------------------------------------------------------------------------------------
a² + b² = c²
-------------------------------------------------------------------------------------
Find the missing leg.
-------------------------------------------------------------------------------------
15² + b² = 18²
b² = 18² - 15²
b² = 99
b = √99
b = 9.95 cm
-------------------------------------------------------------------------------------
Answer: 9.95 cm
-------------------------------------------------------------------------------------